Sources of international legal regulation of electronic document circulation (Journal of actual problems of jurisprudence, 2019)
This article deals with topical issues of legal support of electronic document management in the world practice: sources of international legal regulation of electronic document management. It should be noted that the national regulatory framework governing relations in the field of electronic document management, last but not least depends on the experience of other countries. The legislative experience of other countries is particularly useful when the trends in the development of electronic document flow coincide with the direction of development of the countries whose experience is used. This article providesa comprehensive analysis of international legal acts in this area.The purpose of this study is to analyze the rules of international law governing relations in the fieldof electronic document management. All countries where electronic document flow is regulated canbe divided into 3 blocks. Each block is characterized by its own model of legal regulation of electronicdocument management. The first block is the American model of electronic document management.It is used in USA, Canada and other countries. The second block is the European model. Used by EUmember states. The third block is the post-Soviet model of electronic document management. It is usedin most CIS countries.The authors came to the conclusion that it is necessary to implement the norms of international lawregulating relations in the field of electronic document management in the norms of national legislation.The theoretical and methodological basis of the article is built on the organic combination of therequirements of general scientific and private scientific methodology. In addition, the paper uses privatescientific methods: structural and systematic analysis, specific historical, comparative legal, logical, statisticalmethods, etc.Key words: electronic document, electronic document flow, electronic commerce, electronic signature,electronic message.